Ciencia, cultura y nación: la recepción del darwinismo en la Argentina decimonónica - Pablo Perazzi (Nuevo mundo - Mundos Nuevos, 2011)
The purpose of this article is to examine some aspects of the reception, aclimatization, and circulation of Darwin works in the cultural environment of the Argentina´s nineteenth-century , from their first contact with local scientists to their enthronement as a doctrine of change and progress.Our approach is based in Latin American perspective´s at History of Science: giving priority to local contexts and inquirying the transplant process and acclimatization of scientific ideas, according to the negotiations, tensions and resistance such processes generated among the local scientists.However, our argument remarks that between “transformist” currents wich appeared at “Rioplatense” context, Darwin´s ideas were the most celebrated. But, paradoxically, they didn´t have correlación with scientific work. On the contrary, evolutionism was an political idea against catholic church, but not a body of hypothesis able to permeate the practices of laboratory.